2014
DOI: 10.3892/ol.2014.2000
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma of the nipple: A clinicopathological report of 13 cases

Abstract: Adenoma of the nipple (AN) represents a rare benign mammary proliferation of lactiferous ducts. It appears as an erosive or ulcerative lesion, which in a number of cases is associated with a serous/hematic secretion. AN may be clinically confused with Paget’s disease and histologically with invasive breast carcinoma or breast cancer precursor lesions. Therefore, the histological and immunophenotypic analysis is essential for the differential diagnosis. The present study describes the histopathological characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 12 publications
2
66
2
8
Order By: Relevance
“…Histologically, NA can appear similar to other breast conditions (including syringomatous adenoma of the nipple, intraductal papilloma, adenomyoepithelioma, ductal carcinoma in situ, and invasive ductal carcinoma) as well as several dermatologic lesions (including syringoma of the skin, hidradenoma papilliferum, and syringocystadenoma papilliferum) [ 2 , 15 , 23 , 26 , 52 , 118 , 131 ]. The major histologic features of NAs are that they represent a ductal proliferation of glandlike structures within the stroma of the nipple, and generally have fairly well circumscribed borders but without encapsulation [ 8 , 15 , 23 , 26 , 52 , 118 ]. Sclerosis/fibrosis may distort glands, mimicking an invasive growth pattern.…”
Section: Discussion/reviewmentioning
confidence: 99%
“…Histologically, NA can appear similar to other breast conditions (including syringomatous adenoma of the nipple, intraductal papilloma, adenomyoepithelioma, ductal carcinoma in situ, and invasive ductal carcinoma) as well as several dermatologic lesions (including syringoma of the skin, hidradenoma papilliferum, and syringocystadenoma papilliferum) [ 2 , 15 , 23 , 26 , 52 , 118 , 131 ]. The major histologic features of NAs are that they represent a ductal proliferation of glandlike structures within the stroma of the nipple, and generally have fairly well circumscribed borders but without encapsulation [ 8 , 15 , 23 , 26 , 52 , 118 ]. Sclerosis/fibrosis may distort glands, mimicking an invasive growth pattern.…”
Section: Discussion/reviewmentioning
confidence: 99%
“…In studies conducted by Stormby and Bondeson, 6 Mazzara et al, 7 and Koss et al, 8 aspiration biopsy cytology revealed adenoma of the nipple. 12 When myoepithelial cells are not clearly detected in the cytological specimen, they should be examined using histopathology. First, a large number of cells were isolated from an aspiration biopsy cytology specimen.…”
Section: Discussionmentioning
confidence: 99%
“…The positivity of at least two markers is sufficient for diagnosis, such as p63, CK5/6, hcaldesmon, calponin-1, a-smooth muscle actin, and CD10, with p63 and CK5/6 serving as superior markers. 12 When myoepithelial cells are not clearly detected in the cytological specimen, they should be examined using histopathology. Adenoma of the nipple causes erosion, because of which discriminating it from Paget's disease becomes the primary clinical problem.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with florid papillomatosis of the nipple usually present with a nipple discharge or small superficially located nodule in the nipple-areolar complex. [12][13][14][15] Often, there are associated inflammatory changes in the overlying skin of the nipple, which may be ulcerated and may suggest Paget disease clinically. Florid papillomatosis occurs in both sexes and over the entire age spectrum, including infancy.…”
Section: Clinical Aspectsmentioning
confidence: 99%